قلق الاختبار لدى طلاب كلية الأبيض للعلوم والتقانة في ضوء بعض المتغيرات - آدم, عبد الناصر عبد الرحيم; محمد نور, عبيد الله أحمد الحاج (Gezira Journal of Educational Sciences and Humanities; مجلد 19 عدد 2 (2022), 2023)
هدفت هذه الدراسة إلى الكشف عن قلق الاختبار لدى طلاب كلية الأبيض للعلوم والتقانة في ضوء بعض المتغيرات، من خلال قياس مستوى القلق لديهم واختبار هل تختلف درجات القلق لدى الطلاب وفقاً لاختلاف النوع، العمر، المستوى الأكاديمي؟ ولتحقيق أهداف الدراسة اتبعت الدراسة المنهج الوصفي التحليلي وتكونت عينة الدراسة من (150) طالباً (54) منهم ذكوراً ، (96) منهم إناثاً  تم اختيارهم عن طريق العينة العشوائية الطبقية من مجتمع الدراسة. لتحقيق أهداف الدراسة تم إعداد مقياس قلق الاختبار بناءً على مقياس قائمة قلق الاختبار الذي أعده شارلز سولبيرغ ونقله إلى العربية نبيل الزهار، وتعديله ليلائم بيئة الدراسة. في المعالجات الإحصائية استخدمت الإحصاءات الوصفية، معاملات الارتباط، معادلة ألفا كرونباخ للثبات. لتحليل النتائج استخدم برنامج تحليل الحزم الإحصائية للعلوم الاجتماعية (SPSS). بيَّنت النتائج وجود نسبة قلق عالية ذات دلالة إحصائية عند مستوى (P <0.05). كما بيَّنت النتائج عدم وجود فروق بين طلاب كلية الأبيض للعلوم والتقانة في مستويات قلق الاختبار وفقاً لـ (النوع، أو العمر الزمني، أو المستوى الأكاديمي). أوصت الدراسة بضرورة اهتمام المرشدين النفسيين في مجال التعليم بأثر قلق الاختبار النفسي على الطلبة من النوعين (ذكور/ إناث) في مختلف المستويات الأكاديمية ولكل الفئات العمرية؛ حيث بينت النتائج عدم وجود فروق بين الطلبة وفق تلك المؤشرات، ومعالجة القلق بواسطة برامج الإرشاد التربوي المتعددة.   الكلمات المفتاحية : قلق الأختبار-المتغيرات الديموغرافية -مدينة الأبيض. The objective of this study was to investigate test anxiety among students of Elobeid College for Science and Technology in the light of some variables. Through measure the level of test anxiety and examine whether there were differences in test anxiety due to; gender, age and academic level. The study followed the analytical descriptive method. A simple random sample of (150) students were involved (54) of them were males and (96) were females. To achieve the objectives of the study test anxiety scale been prepared in the basis of Charles Solberg Test Anxiety list that translated to Arabic by Nabeel Alzhar and modified to be adopted to study area. For statistical analysis; descriptive analysis, Pearson correlation coefficient and alpha Chronbach were calculated via "Statistical Package for Social Sciences" (SPSS) programme. Results revealed that there was a high significant test-anxiety level among students while there were no significant differences between students due to (gender, age or academic level). The study recommended that psychological counselors in the field of education should pay attention to the impact of psychological test anxiety on students, gender (male / female) at various academic levels and for all age groups. The results showed that there were no differences between students according to these indicators, and anxiety was addressed by means of various educational counseling programs.